Can a sociolinguistic perspective of Second Language Acquisition solve 'the longstanding human curiosity' of learning languages? - Isabelle Sophie Thaler (Peoples' Friendship University of Russia (RUDN University), 2019)
The present paper looks into SLA research which has been overwhelmed with multitude of competing theories, thus making it plausible that none of them alone can explain the complex issue to a satisfying extent. Following the search for complementarity, this study seeks to show how a sociolinguistic approach contributes to the understanding of SLA, by pointing to gains as well as to limitations of applying only such an approach. Responding to the appeal for an enhancement of using sociolinguistic as well as socio-cognitive theories, this paper pursues this endeavour by critically analysing a sociolinguistic approach and zooming in on research on two articles - by Soltani (2018) and Anderson (2017) - about study abroad in Anglophone countries. The author argues that although the two studies are focused on a specific group of learners in specific circumstances and might not have contributed to an improvement in a narrow view of SLA, they have highlighted the need to put cognitive theories into a socialisation perspective and to recognise that similar issues might arise when other target groups such as EFL secondary school students go abroad on a school exchange and are confronted with socialisation into family, school or peers. The paper concludes that if sociolinguistic approaches seek a holistic account of the complexities of second language learning, they should adapt to new developments and collaborate with cognitive theories.